"Enemies of the people": Populist performances in the Daily Mail reporting of the Article 50 case. (October 2018) - Breeze, Ruth
Highlights: Representation of social actors underpins ideology in media discourse. Pro-Brexit discourses in the Daily Mail drive powerful identification with "the people". Discursive strategies project Establishment figures as "enemies of the people". A productive symbiosis emerges between political and tabloid populism.